153 A common disease but a rare cause of lumbosacral plexopathy. Issue 3 (9th February 2012) - Ali, R; Torella, F; Nahser, H; Davies, R
Abstract : Ischaemic injury to the lumbosacral plexus is rare, given the plexus' rich blood supply and the low metabolic demand of the peripheral nerve tissue. There are some 80 cases in the literature, most occurring acutely after aorta–iliac reconstruction. We describe a patient who developed lumbosacral plexopathy secondary to extensive peripheral vascular disease. A 58-year-old female smoker developed pelvic and lower back pain with intermittent numbness over the right thigh. The initial neurological examination and the MRI of the lumbosacral spine were normal. Two months later, she had developed urinary hesitancy and the right knee jerk was absent. Neurophysiological examination showed an asymmetrical lumbosacral plexopathy. Repeat clinical examination found absent ankle jerks, with both knee jerks now being present. The pedal pulses were reduced but the feet were well perfused (warm to touch and capillary refill intact). Extensive blood tests and CT of the chest, abdomen and pelvis were normal. Cerebrospinal (CSF) examination showed only mildly elevated protein, at 0.66 g/l (NR 0.15–0.45 g/l). Dural arteriovenous fistula was suspected based on visualisation of abnormal vessels at T9/10–T11/12. Spinal angiography via the femoral approach, however, proved impossible due to severe arteriosclerotic disease. Subsequent CT angiography of the aorta found complete occlusion of the lumbar aorta below the origin of renal arteries. Supra-coeliac aorto-bifemoral bypass with left iliac re-implantation led to an improvement in her symptoms. Chronic ischaemia of the lumbosacral plexus is rarely described; it can present with intermittent pain and sensorimotor impairments.